Effects of Dietary Protein and Polysaccharide Fortification on Disease - Luo, Yongting; Luo, Junjie (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Proteins and polysaccharides are two kinds of versatile natural macromolecules that are ubiquitous in nature. A tailored diet fortified with proteins and polysaccharides has been developed to ameliorate a wide array of diseases. This reprint contains experimental studies, reviews and systemic reviews that cover all beneficial aspects related to protein or polysaccharide fortification, especially for the treatment of various disorders and their complications.